2011
DOI: 10.1007/s00248-011-9869-9
|View full text |Cite
|
Sign up to set email alerts
|

The Lignicolous Fungus Coniochaeta pulveracea and Its Interactions with Syntrophic Yeasts from the Woody Phylloplane

Abstract: The yeast-like fungus Coniochaeta pulveracea was studied with regard to its novel lignocellulolytic activities and the possible effect thereof on yeasts from the woody phylloplane. An enrichment procedure was used to isolate C. pulveracea from a decaying Acacia tree, and the identity of the isolate was confirmed using morphology, as well as molecular and phylogenetic techniques. This isolate, as well as strains representing C. pulveracea from different geographical regions, were compared with regard to optimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…The filamentous nature of C. pulveracea on a solid growth medium incubated at its optimum growth temperature of 30°C (Van Heerden et al 2011) was confirmed by studying the morphology of C. pulveracea CAB683, CBS110471 and CBS114628 on oatmeal agar (OA) using light-and scanning electron microscopy. Material for scanning electron microscopy was fixed with 3 % (v/v) glutardialdehyde (Merck, Darmstadt, Germany) dissolved in 0.1 mol/L sodium phosphate buffer at pH 7.0 for 4 h. The fixed material was subsequently rinsed twice for 10 min with the phosphate buffer.…”
Section: Effect Of Physical Parameters On Dimorphic Switchingmentioning
confidence: 99%
See 4 more Smart Citations
“…The filamentous nature of C. pulveracea on a solid growth medium incubated at its optimum growth temperature of 30°C (Van Heerden et al 2011) was confirmed by studying the morphology of C. pulveracea CAB683, CBS110471 and CBS114628 on oatmeal agar (OA) using light-and scanning electron microscopy. Material for scanning electron microscopy was fixed with 3 % (v/v) glutardialdehyde (Merck, Darmstadt, Germany) dissolved in 0.1 mol/L sodium phosphate buffer at pH 7.0 for 4 h. The fixed material was subsequently rinsed twice for 10 min with the phosphate buffer.…”
Section: Effect Of Physical Parameters On Dimorphic Switchingmentioning
confidence: 99%
“…These strains, together with the yeast strains used in the co-culture study, are listed in Table 1. The strain CAB683 was isolated from an Acacia tree in the Northern Cape of South Africa using an enrichment broth containing molasses, chopped wheat straw and chloramphenicol (Van Heerden et al 2011). Cryptococcus neoformans CAB935 originated from a nearby tree, while Cryptococcus neoformans CAB858 was originally isolated from a clinical sample taken from a patient suffering from HIV/AIDS.…”
Section: Strains and Growth Conditionsmentioning
confidence: 99%
See 3 more Smart Citations